APOE-ε4 Genotype is Associated with Elevated Post-Concussion Symptoms in Military Veterans with a Remote History of Mild Traumatic Brain Injury. (6th December 2018) - Merritt, Victoria C; Lapira, Kristina M; Clark, Alexandra L; Sorg, Scott F; Werhane, Madeleine L; Jak, Amy J; Bondi, Mark W; Schiehser, Dawn M; Delano-Wood, Lisa
Abstract: Objective: We evaluated the influence of the APOE-ε4 allele on post-concussive symptoms in military Veterans with a remote history of mild traumatic brain injury (mTBI). Method: Participants ( N = 77) were administered neuropsychiatric measures, on average, approximately 5 years following their most recent mTBI and provided a DNA sample for APOE genotyping. Veterans were divided into two groups based on their ε4 status ( n = 14 ε4+, n = 63 ε4–). The Neurobehavioral Symptom Inventory (NSI) was the primary outcome measure, from which a total score was derived, as well as three symptom clusters (somatic, cognitive, and affective). Results: ANCOVAs showed a significant main effect of ε4 genotype on the NSI total score and somatic symptom cluster after adjusting for posttraumatic stress symptoms and mTBI history ( p = .019–.028, ηp 2 = .064–.073), such that ε4+ Veterans endorsed significantly greater symptoms than ε4– Veterans. Conclusions: Our findings suggest that genetic risk may help to explain the poorer long-term outcomes often observed in this population.